High-temperature oxidation behaviors and mechanisms in newly designed L12-strengthened high-entropy alloys. (November 2022) - Hou, Jinxiong; Tan, Yi; Liu, Shaofei; Zhang, Jianyang; Xiao, Weicheng; Kong, Haojie; Li, Qian; Cao, Boxuan; Luan, Junhua; Zhao, Yilu; Kai, Jijung; Yang, Tao
Abstract: The oxidation behaviors of a newly-designed L12 -strengthened multi-component Ni-Co-Fe-Cr-Al-Ti-Nb system were studied at 800 ℃, where the synergistic alloying effects of Ti, Nb, and Cr on the oxidation resistance were uncovered. The findings show that the doping of Ti facilitates the outward diffusion of metal cations and inward diffusion of oxygen ions through the Cr2 O3 and Al2 O3 scales, deteriorating the oxidation resistance. By substituting the Ti with Nb, a continuous and dense Al2 O3 scale was potentially promoted benefiting from the "unlocked" Al atoms from the L12 particles. The increased additions of Cr and Nb contribute to the improved oxidation resistance. Highlights: Excellent strength and ductility combinations were achieved in this L12 -strengthened high-entropy alloy (HEA) system. The element-mediated oxidation behaviors and mechanisms in the L12 -strengthened HEAs were studied. The doping of Ti facilitates the outward and inward diffusions of ions through the Cr2 O3 and Al2 O3 scales. The elevated additions of Cr and Nb contribute to the improved oxidation resistances for high-temperature applications.